A new genus of oak gallwasps, Cycloneuroterus Melika & Tang, with the description of five new species from Taiwan (Hymenoptera: Cynipidae: Cynipini) - Tang, Chang-Ti; Melika, George; Nicholls, James A.; Yang, Man-Miao; Stone, Graham N. (Zootaxa, 2011)
A new genus of cynipid oak gallwasp, Cycloneuroterus Melika & Tang (Hymenoptera: Cynipidae: Cynipini), containing five new species, C. lilungi, C. longinuxus, C. lirongchiuea, C. fortuitusus and C. formosanus, is described from Taiwan. Diagnostic characters and generic limits of the new genus are discussed in detail and a key to a group of closely related genera which share a suite of diagnostic genus-level characters is given. Descriptions of galls and adults, data on the diagnosis, distribution, host plant associations and biology of the new species, and a key to all five species are given.